Rubén Darío y Dreyfus: confusión y desencuentro - Claire Pailler (Caravelle)
Darío, fascinated by French life, and even before settling in Paris in 1899, acting as a correspondent of La Nacion from Buenos Aires, cannot avoid mentioning the event that is deeply distressing France’s society at the time: the Dreyfus Affair. His chronicles reveal the sources where he found his information –often chosen among the French opposed to Dreyfus– and indicate a certain casualness as well as his difficulty to understand the heavy stakes of this moral, social and political crisis.